2008
DOI: 10.1016/j.juro.2008.03.114
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele in Adolescents: A 6-Year Longitudinal and Followup Observational Study

Abstract: Children with varicocele should be regularly monitored to identify varicocele grade, testicular volume and vein reflux grade, and management should be determined accordingly. Spontaneous venous reflux toward the testis independent of varicocele grade closely correlates with the onset of testicular hypotrophy and abnormal semen analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…30 One study has focused specifically on the correlation between hemodynamic grade and pubertal development, testicular vein reflux, and semen quality in adolescent patients. 36 All patients who developed hypotrophy and testicular asymmetry during followup in this study had spontaneous venous reflux on CDUS that was classified as high hemodynamic grade.…”
Section: Hemodynamic Grading Systemsmentioning
confidence: 90%
“…30 One study has focused specifically on the correlation between hemodynamic grade and pubertal development, testicular vein reflux, and semen quality in adolescent patients. 36 All patients who developed hypotrophy and testicular asymmetry during followup in this study had spontaneous venous reflux on CDUS that was classified as high hemodynamic grade.…”
Section: Hemodynamic Grading Systemsmentioning
confidence: 90%
“…[17][18][19] Since for postoperative evaluation in pediatric age, semen analysis cannot be performed, testicular catch-up volume is the most important parameter in evaluating the outcome of varicocelectomy. [9] Some investigators have reported recovery of testicular development, and sperm dysfunction after varicocelectomy. [10,20,21] Sinanoğlu et al [10] followed up 39 adolescents with varicocele at 3 month-intervals after varicocelectomy just by calculating testicular volumes.…”
Section: Discussionmentioning
confidence: 99%
“…[8] As an accepted strategy in adolescent varicocele treatment should be instituted in case of ipsilateral testicular hypotrophy. [7,9] In these patients, indications for surgical intervention are debatable, more than 20% difference in testicular size relative to the intact testis, abnormalities in sperm parametres, and painful varicoceles have been asserted as indications for surgical intervention. [3] In infertile men, subinguinal microsurgery has become an gold standard approach for spermatic vein ligation in infertile men with lower complication, and recurrence rates relative to other techniques, however the place of this approach in adolescent population is still debatable.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also demonstrated that there is a clear increase in testicular size in adolescent subjects following surgical repair as well as a resumed growth of the testicle (Zampieri, 2008;Zampieri and Cervellione, 2008).…”
Section: Testicular Volume Diseases and Fertility Potentialmentioning
confidence: 99%